Natural variability and anthropogenic trends in oceanic oxygen in a coupled carbon cycle-climate model ensemble - Frölicher, T. L.; Joos, F.; Plattner, G.-K.; Steinacher, M.; Doney, S.C. (Global Biogeochemical Cycles, 2009)
Internal and externally forced variability in oceanic oxygen (O2) are investigated on different spatiotemporal scales using a six-member ensemble from the National Center for Atmospheric Research CSM1.4-carbon coupled climate model. The oceanic O2 inventory is projected to decrease significantly in global warming simulations of the 20th and 21st centuries. The anthropogenically forced O2 decrease is partly compensated by volcanic eruptions, which cause considerable interannual to decadal variability. Volcanic perturbations in oceanic oxygen concentrations gradually penetrate the ocean’s top 500 m and persist for several years. While well identified on global scales, the detection and attribution of local O2 changes to volcanic forcing is difficult because of unforced variability. Internal climate modes can substantially contribute to surface and subsurface O2 variability. Variability in the North Atlantic and North Pacific are associated with changes in the North Atlantic Oscillation and Pacific Decadal Oscillation indexes. Simulated decadal variability compares well with observed O2 changes in the North Atlantic, suggesting that the model captures key mechanisms of late 20th century O2 variability, but the model appears to underestimate variability in the North Pacific. Our results suggest that large interannual to decadal variations and limited data availability make the detection of human-induced O2 changes currently challenging.